2011
DOI: 10.1128/aac.00978-10
|View full text |Cite
|
Sign up to set email alerts
|

Activities of TMC207, Rifampin, and Pyrazinamide against Mycobacterium tuberculosis Infection in Guinea Pigs

Abstract: The experimental compound TMC207 is showing promise against infections caused by Mycobacterium tuberculosis both in a variety of animal studies and in the field. In this study, we used the guinea pig model, a species that shows several similarities to human tuberculosis, including the hallmark of primary granuloma necrosis, to determine the efficacy of a combination regimen combining TMC207 with rifampin and pyrazinamide. This drug regimen rapidly reduced the bacterial load in the lungs to undetectable levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 30 publications
4
29
0
1
Order By: Relevance
“…In the current study, mycobacteria were still detectable in the spleens of guinea pigs assessed at relapse after 2 months of RHZ or PHZ, indicating that TB infection was not eradicated in these animals. Difficulty in sterilizing M. tuberculosis-infected guinea pig tissues was also observed by Shang et al, who showed that although a combination regimen containing the novel diarylquinolone TMC207 with R and Z rapidly reduced the bacillary load in the lungs to undetectable levels by 8 weeks of treatment, more than one fifth of animals developed clinical relapse as late as 11 months after the treatment was discontinued (32). The reason for the inferior activity of the two rifamycin-containing regimens against M. tuberculosis in the spleens relative to the lungs observed in the current study requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…In the current study, mycobacteria were still detectable in the spleens of guinea pigs assessed at relapse after 2 months of RHZ or PHZ, indicating that TB infection was not eradicated in these animals. Difficulty in sterilizing M. tuberculosis-infected guinea pig tissues was also observed by Shang et al, who showed that although a combination regimen containing the novel diarylquinolone TMC207 with R and Z rapidly reduced the bacillary load in the lungs to undetectable levels by 8 weeks of treatment, more than one fifth of animals developed clinical relapse as late as 11 months after the treatment was discontinued (32). The reason for the inferior activity of the two rifamycin-containing regimens against M. tuberculosis in the spleens relative to the lungs observed in the current study requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Studies using multiple animal models have shown that bedaquiline is efficacious against M. tuberculosis, Mycobacterium leprae, and to some extent M. avium (25,(35)(36)(37). Bedaquiline potently inhibits the mycobacterial enzyme complex ATP synthase, thus interfering with energy production and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…A new and approved cephalosporin is ceftobiprole that is active against methicillin-resistant S. aureus and is not hydrolyzed by a number of β-lactamases from Gram-positive bacteria. 100 Another antibiotic of note is cerulenin, an antifungal agent produced by Acremonium caerelens. It was the first inhibitor of fatty acid biosynthesis discovered.…”
Section: Antimicrobialsmentioning
confidence: 99%